Unpacking the Impact of Customer Perceived Value and Competitive Advantage on Customer Loyalty: The Mediating Role of Trust - Basrowi Basrowi; Juhary Ali; Tulus Suryanto (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
New studies are needed to illuminate the factors that affect customer satisfaction when using sharia banking services in Indonesia. This is especially significant given the existing study gap regarding Indonesia's relatively low number of sharia bank customers, despite the country's predominantly Muslim population. Instead, many of them prefer to use conventional banks, highlighting the need for a deeper understanding of the reasons behind this trend. This study examined the impact of customer perceived value and competitive advantage on customer loyalty mediated by trust. This investigation employed a quantitative methodology to examine the relationship between consumers' perceived value, competitive advantage, trust, and customer loyalty. The participants of this study were selected from the customer of Bank Syariah Indonesia (BSI), and data were collected through a questionnaire. The sample size was 210, and the researchers utilized random sampling to select participants. To analyze the collected data, the researchers employed structural equation modeling (SEM) analysis. The study results indicate that perceived value, competitive advantage, and trust significantly impact customer loyalty. This study also shows the mediating role of trust in the relationship between variables.